2016
DOI: 10.1515/jvetres-2016-0052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fertility effect of hydro-alcoholic extract of fennel (Foeniculum vulgare Mill) seed in male Wistar rats

Abstract: Introduction:The study aimed to investigate the anti-fertility effect of fennel (Foeniculim vulgare Mill) seed extract in male rats. Material and Methods: Forty Wistar rats were divided into five equal groups. The control group received distilled water and the experimental groups were orally administered 1 ml of hydro-alcoholic extract of fennel seed in four doses of 35, 70, 140, and 280 mg/kg/b.w. daily for 60 days. After the last gavage, the rats were anaesthetised and the caudal part of the right epididymis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…Minding that, any reduction in spermatogenesis and/or spermiogenesis processes remarkably affects total sperm volume, it is logic to suggest that, the FVEO‐reduced differentiation and miogenesis of germ cells could fairly affect sperm count. In corroboration with our findings, Mansouri and co‐workers showed that, the hydro‐alcoholic extract of FV (at dose levels of 70, 140, and 280 mg kg −1 ) reduces spermatogonial cells population and remarkably diminishes sperm count versus control rats . However, the question is that, how does the FVEO impact the spermatogenesis?…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Minding that, any reduction in spermatogenesis and/or spermiogenesis processes remarkably affects total sperm volume, it is logic to suggest that, the FVEO‐reduced differentiation and miogenesis of germ cells could fairly affect sperm count. In corroboration with our findings, Mansouri and co‐workers showed that, the hydro‐alcoholic extract of FV (at dose levels of 70, 140, and 280 mg kg −1 ) reduces spermatogonial cells population and remarkably diminishes sperm count versus control rats . However, the question is that, how does the FVEO impact the spermatogenesis?…”
Section: Discussionsupporting
confidence: 91%
“…However, the question is that, how does the FVEO impact the spermatogenesis? Indeed, not all but some previous findings have illustrated that, the flavonoids (albeit at higher levels) are able to inhibit cell division or stimulate apoptosis by restraining the DNA replication . In line with this issue, several previous studies have shown that, the flavonoid inhibit the K562, HeLa, EC‐109, NCI‐H446 cells, A549, and human colon cancer cell lines proliferation in a dose‐dependent manner.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this regard, there has been a renewed interest in the approaches of traditional medicine and phytotherapy in medical arena. Medicinal plants and their derivatives have been studied, by the application of scientific approaches, in vitro, with animals, and ultimately in clinical trials so that more efficient therapeutic approaches and drugs can be discovered [16][17][18][19][20][21][22][23][24][25][26] . Apart from drug therapy, other methods are used in tinnitus therapy such as phytotherapy (Table 2).…”
Section: Medicinal Plants and Tinnitusmentioning
confidence: 99%
“…Local people use them for prevention and treatment of various disorders [16][17][18][19][20][21][22][23][24][25][26] . Also researchers have evaluated and confirmed their therapeutic properties [27][28][29][30][31] . They can be used to produce more effective drugs if they are investigated in additional studies [32][33][34][35][36] .…”
mentioning
confidence: 99%